Seeing Sacred for Centuries: Digitally Modeling Greek Worshipers’ Visualscapes at the Argive Heraion Sanctuary - Susmann Natalie M. (Open Archaeology)
Mount Akraia, located in the northeastern Greek Peloponnese, hosted an open-air worshiping site beginning in the tenth/ninth c BCE. The space gained popularity and was quickly transformed into a monumental sanctuary known as the Argive Heraion. The sanctuary is elevated and easy to spot from a distance; it provides unobstructed views of the surrounding region. The location is historically significant as well, overlying a Mycenaean cemetery and settlement. Ancient authors frame the Argive Heraion as a touchstone sacred landmark; contemporary scholars echo these descriptions. This article synthesizes the textual and material record, questioning which of the Argive Heraion’s visual characteristics captivated worshipers’ senses, and if worshipers’ perceptions shifted over time. My complete dataset spans the tenth–second c BCE and considers all other places where group worship happened in the Argive Plain. Using GIS and text analyses, I measure and compare an array of viewing experiences that were culturally meaningful for Greek worshipers. The resultant models compare the Argive Heraion’s visualscape over time, framed against the broader sacred landscape. I also look to the present day. Using contemporary tourist reviews, I unpack nuances that are missing in the archaeological and historical record. Personal histories shift what we see and how we see it.